Inteligência emocional e sua relação com ansiedade, depressão e burnout em trabalhadores assistenciais - Souza, Bruna de (Universidade Federal de São Carlos, 2024)
Emotional Intelligence (EI) is the processing of emotional information that includes perception, use, knowledge, and regulation of emotions. EI can play a protective role against challenges related to mental health, notably in the face of emerging demands such as anxiety, depression, and burnout. Previous investigations have established a relationship between EI and these psychological challenges, especially among assistance workers, whose occupations expose them to greater impairment of these variables. Therefore, this research aims to examine the relationship between EI and levels of anxiety, depression, and burnout in assistance professionals, including nurses, psychologists, teachers, and bank clerks. The study included the participation of 207 professionals, distributed among bank clerks (n = 34), nurses (n = 55), teachers (n = 61), and psychologists (n = 57), with an average age of 32.93 years (SD = 8.00). The majority of participants were female (62.32%, n = 129). The participation criteria included having a higher education level and being actively employed during the study. Data collection was conducted through the online application of the following instruments: DSM-5 Self-Rated Level 1 Cross-Cutting Symptom Measure—Adult (PROMIS I), DSM-5 Self-Rated Level 2 Cross-Cutting Symptom Measure—Depression (PROMIS II Depression), Maslach Burnout Inventory (MBI), Emotional Skills Inventory (ESI), and Brazilian Economic Classification Criteria. The main results showed negative and moderate correlations between EI and Burnout (Emotional Exhaustion and Cynicism); negative and moderate correlations between EI and Anxiety. Additionally, positive and moderate correlations were observed between EI and Burnout (Professional Efficacy), and EI showed a low negative correlation with Depression. Nurses demonstrated the highest levels of anxiety and depression, while psychologists exhibited higher EI. This study highlights the importance of EI as a relevant process for the adequate care and attention to people's mental health.
Emotional intelligence and its relationship with anxiety, depression and burnout in care workers
Keywords: Inteligência emocional; Ansiedade; Depressão; Burnout; Trabalhadores assistenciais; Emotional intelligence; Anxiety; Depression; Burnout; Assistance workers; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA COGNITIVA